2013
DOI: 10.1002/cphc.201300219
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Structure and Dynamics of Biomolecules by Using Soluble Paramagnetic Probes

Abstract: Characterisation of the structure and dynamics of large biomolecules and biomolecular complexes by NMR spectroscopy is hampered by increasing overlap and severe broadening of NMR signals. As a consequence, the number of available NMR spectroscopy data is often sparse and new approaches to provide complementary NMR spectroscopy data are needed. Paramagnetic relaxation enhancements (PREs) obtained from inert and soluble paramagnetic probes (solvent PREs) provide detailed quantitative information about the solven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 89 publications
(145 reference statements)
0
52
0
Order By: Relevance
“…However, a discordant result was obtained when the lipophilic 16-DSA was used as the paramagnetic probe (note that an apolar probe was not employed in the previous study (Kim et al, 2012) of the isolated β3 TM): for 16-DSA, little difference was observed between the membrane topology and tilt of β3-WT and the β3-K716E mutant (Figure 4C and Figure 4—figure supplement 1). This led us to recall literature showing that chelate probes such as Mn(II)-EDDA and Gd(III)-DTPA sometimes have an exposed ligand site that can transiently associate with anions such as Glu and Asp side chain carboxylates (Hocking et al, 2013). To test this possibility, we repeated the Gd(III)-DTPA probe experiment under conditions in which excess (10 mM) free EDTA was added to the solution to cap any free ligand sites in Gd(III)-DTPA, thereby suppressing any direct binding of protein carboxyl sides to the open ligand site in the lanthanide ion chelate.…”
Section: Resultsmentioning
confidence: 99%
“…However, a discordant result was obtained when the lipophilic 16-DSA was used as the paramagnetic probe (note that an apolar probe was not employed in the previous study (Kim et al, 2012) of the isolated β3 TM): for 16-DSA, little difference was observed between the membrane topology and tilt of β3-WT and the β3-K716E mutant (Figure 4C and Figure 4—figure supplement 1). This led us to recall literature showing that chelate probes such as Mn(II)-EDDA and Gd(III)-DTPA sometimes have an exposed ligand site that can transiently associate with anions such as Glu and Asp side chain carboxylates (Hocking et al, 2013). To test this possibility, we repeated the Gd(III)-DTPA probe experiment under conditions in which excess (10 mM) free EDTA was added to the solution to cap any free ligand sites in Gd(III)-DTPA, thereby suppressing any direct binding of protein carboxyl sides to the open ligand site in the lanthanide ion chelate.…”
Section: Resultsmentioning
confidence: 99%
“…[5] ThesPRE technique has been used to assess the structures of proteins and protein complexes. [5] ThesPRE technique has been used to assess the structures of proteins and protein complexes.…”
mentioning
confidence: 99%
“…Gd(DTPA-BMA) is an inert, water-soluble, paramagnetic compound that displays no specific binding to micelles or peptides (20,58). In solution, this compound enhances the relaxation rates of nuclei exposed to solvent through PRE.…”
Section: Analysis Of Trp3 Dynamics By Means Of Relaxation Parametersmentioning
confidence: 99%
“…PRE measurements can provide information about the orientation of peptides inserted in micelles (20,58). As proposed by Respondek et al (20), PRE experimental values can be modeled by Eq.…”
Section: Analysis Of Peptide Location and Orientation In The Micellesmentioning
confidence: 99%